2015
DOI: 10.1186/s12896-015-0226-9
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale production and antiviral efficacy of multi-target double-stranded RNA for the prevention of white spot syndrome virus (WSSV) in shrimp

Abstract: BackgroundRNA interference (RNAi) is a specific and effective approach for inhibiting viral replication by introducing double-stranded (ds)RNA targeting the viral gene. In this study, we employed a combinatorial approach to interfere multiple gene functions of white spot syndrome virus (WSSV), the most lethal shrimp virus, using a single-batch of dsRNA, so-called “multi-WSSV dsRNA.” A co-cultivation of RNase-deficient E. coli was developed to produce dsRNA targeting a major structural protein (VP28) and a hub … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 37 publications
(48 reference statements)
1
36
0
2
Order By: Relevance
“…Viral protein ini berpeluang untuk dijadikan sebagai vaksin rekombinan (Sánchez-Paz, 2010). Teknologi interferensi RNA (RNAi) merupakan teknik vaksinasi DNA rekombinan yang spesifik dan efektif untuk menghambat replikasi virus dengan introduksi small interference (si)RNA maupun double-stranded (ds)RNA pada target gen virus (Haq et al, 2012;Jayachandran et al, 2012;Thammasorn et al, 2015). Teknologi vaksinasi menggunakan agen virus dsRNA berkembang sangat pesat terutama dibidang medis, pertanian, dan akuakultur (Jin et al, 2010;Lichner et al, 2003;Rowley & Pope, 2012).…”
Section: Pendahuluanunclassified
“…Viral protein ini berpeluang untuk dijadikan sebagai vaksin rekombinan (Sánchez-Paz, 2010). Teknologi interferensi RNA (RNAi) merupakan teknik vaksinasi DNA rekombinan yang spesifik dan efektif untuk menghambat replikasi virus dengan introduksi small interference (si)RNA maupun double-stranded (ds)RNA pada target gen virus (Haq et al, 2012;Jayachandran et al, 2012;Thammasorn et al, 2015). Teknologi vaksinasi menggunakan agen virus dsRNA berkembang sangat pesat terutama dibidang medis, pertanian, dan akuakultur (Jin et al, 2010;Lichner et al, 2003;Rowley & Pope, 2012).…”
Section: Pendahuluanunclassified
“…On the other hand, Thammasorn et al. () orally administered dsRNA‐vp28 (12 μg/g food) to 3–5 g L. vannamei shrimp and challenged them with WSSV, finding 70% of protective effect. Finally, with the specific dsRNA expression system obtained from the microalgae Chlamydomonas reinhardtii , 13% of protective was obtained using 10 8 dsRNA‐RdRP‐expressing microalgae/gr food in 0.1‐g L. vannamei shrimp.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, researchers in Thailand recently succeeded in using RNAi by oral delivery against WSSV infection in P. monodon , leading to reduced percentages in cumulative mortality and delayed average time of death (Thammasorn et al . ).…”
Section: Applicationsmentioning
confidence: 99%
“…While the studies on the applicability of RNAi to control the virus were mostly conducted on a small scale, the success of these experiments clearly showed that RNAi has enormous potential in inhibiting the replication of the virus and improve the survival of shrimp. In fact, researchers in Thailand recently succeeded in using RNAi by oral delivery against WSSV infection in P. monodon, leading to reduced percentages in cumulative mortality and delayed average time of death (Thammasorn et al 2015).…”
Section: Disease Controlmentioning
confidence: 99%